Analysis of the postural stability in individuals with or without signs and symptoms of temporomandibular disorder - Lilian Gerdi Kittel Ries; Fausto Bérzin (Sociedade Brasileira de Pesquisa Odontológica, 2008)
The objective of this study was to evaluate the stability and the distribution of weight of individuals with TMD (Temporomandibular Disorder) when placed in an orthostatic position. Forty female volunteers, participating in this study, were distributed into a control and a TMD group. Clinical examinations of the craniomandibular system and of the neck were performed. Postural stability was evaluated using a stabilographic platform. Through this system, the sway index (SI), the maximum medial-lateral distance (MMLD), the maximum anterior-posterior distance (MAPD) and the medial-lateral symmetry (MLS) could be determined. Tests were performed in the mandibular rest position and during isometric and isotonic contraction. The variables were analyzed through repeated measures ANOVA. The level of significance was p < 0.05. The results of this study indicate that individuals with TMD present more pain in the cervical region (p < 0.05). The group with TMD showed a significant reduction in SI (p < 0.05), MMLD (p < 0.05) and MLS (p < 0.01). Individuals with TMD presented greater postural asymmetry, and cervical pain demonstrated a potential link with an increase in postural stability.